134 Apathy in cerebrovascular small vessel disease is characterised by distinct white matter tract changes. Issue 6 (27th May 2022) - Saleh, Youssuf; Heron, Campbell le; Veldsman, Michele; Drew, Daniel; Plant, Olivia; Schulz, Ursula; Sen, Arjune; Manohar, Sanjay; Rothwell, Peter; Husain, Masud
Abstract : Introduction: Clinical apathy is a poorly understood neuropsychiatric syndrome characterised by a sig- nificant decrease in goal-directed, motivated behaviour. It occurs in 30% of patients with cerebrovas- cular small vessel disease (SVD). With the aim of improving our mechanistic understanding of apathy, we conducted a multimodal investigation combining validated behavioural paradigms and magnetic resonance imaging (MRI) techniques. Methods: 83 patients with MRI evidence of SVD were recruited from the Oxford Vascular Study (OXVASC) and Oxford neurology clinics. They were investigated using a novel effort-based decision making task and the Apathy Evaluation Scale (AES). Structural and diffusion weighted MRI was conducted to measure white matter lesion load (WMLL) and tract integrity, indexed by Fractional anisotropy (FA). Results: Patients with apathy demonstrated a significant reduction in motivated behaviour and were sig- nificantly less incentivised by low levels of reward. Diffusion weighted imaging demonstrated that apathy was characterised by focal changes to limbic association tracts, including the uncinate fasciculus and cingulum bundle, as well as fronto-striatal white matter tracts. Importantly, global measures of disease severity did not independently associate with apathy. Discussion: Reduced incentivisation by low reward characterised apathy in SVD, as previously reported in Parkinson's disease, suggesting a common mechanism underlying apathy across neurological diseases. The association of apathy with focal white matter tract changes is consistent with disruption to key frontal and fronto-striatal circuits which have been previously implicated in effort-based decision-making for rewards. youssuf.saleh@ndcn.ox.ac.uk